Engagement techniques and playing level impact the biomechanical demands on rugby forwards during machine-based scrummaging - Preatoni, E.; Stokes, K. A.; England, M. E.; Trewartha, G. (British Journal of Sports Medicine, 2015)
Objectives: This cross-sectional study investigated the factors that may influence the physical loading on rugby forwards performing a scrum by studying the biomechanics of machine-based scrummaging under different engagement techniques and playing levels. Methods: 34 forward packs from six playing levels performed repetitions of five different types of engagement techniques against an instrumented scrum machine under realistic training conditions. Applied forces and body movements were recorded in three orthogonal directions. Results: The modification of the engagement technique altered the load acting on players. These changes were in a similar direction and of similar magnitude irrespective of the playing level. Reducing the dynamics of the initial engagement through a fold-in procedure decreased the peak compression force, the peak downward force and the engagement speed in excess of 30%. For example, peak compression (horizontal) forces in the professional teams changed from 16.5 (baseline technique) to 8.6 kN (fold-in procedure). The fold-in technique also reduced the occurrence of combined high forces and head-trunk misalignment during the absorption of the impact, which was used as a measure of potential hazard, by more than 30%. Reducing the initial impact did not decrease the ability of the teams to produce sustained compression forces. Conclusions: De-emphasising the initial impact against the scrum machine decreased the mechanical stresses acting on forward players and may benefit players` welfare by reducing the hazard factors that may induce chronic degeneration of the spine.